"Now the Work Begins": Gender Equality in Sámi Politics - Pedersen, Linn-Marie Lillehaug (UiT Norges arktiske universitet, 2014)
This study examines gender equality in Sámi politics after 2005, the year the Sámi Parliament achieved balanced gender representation. The project seeks to answer the question: Within the context of Sámi politics, how is gender equality represented and addressed? To answer this question, the study is based on official documents by the Sámi Parliament and the women’s organization Sámi NissonForum, as well as six semi-structured interviews with Sámi politicians and Sámi women’s activists. Qualitative content analysis is the chosen tool utilized to analyze the respective data, which is divided into two separate sections, firstly a document analysis, and secondly an analysis of the interviews. The findings in this study indicate that gender equality still has a relevant position in Sámi politics, and has become a more integrated part in the work of the Sámi Parliament after 2005. Further, the findings suggest that the political field of equality has expanded after the achievement of gender balanced representation, and issues concerning sexual orientations and domestic violence are included. Also, the study findings reveal that gender equality as a concept has been developed and contextualized within a Sámi political framework, where the concept self-determination is explored through a gender perspective.